A Comparative Study of Laparoscopic Bariatric Surgery : An Iraqi Experience - Mukhtar, Ramiz S. (Journal of the Faculty of Medicine Baghdad, 2013)
Summary: Background: The World Health Organization has declared that obesity is a disease of pandemic significance. The number of performed bariatric procedures has rapidly and considerably increased over the past decade. The most frequently performed and best studied procedures are laparoscopic gastric banding (LAGB), laparoscopic sleeve gastrectomy (LSG) and laparoscopic Roux-en-Y gastric bypass (LRYGB). Objectve: To provide a critical appraisal of the most important scientific evidence comparing the short term outcomes of these three weight-reduction procedures (laparoscopic gastric banding (LAGB), laparoscopic sleeve gastrectomy (LSG), and laparoscopic Roux-en-Y bypass (LRYGB)) using retrospectively collected data for patients with morbid obesity in Iraq. Patients and Methods: Between August 2010 and November 2012, three types of bariatric operations (LAGB, LSG, LRYGB) were performed in a hospital in Baghdad for patients with morbid obesity by the same team. A total of 32 patients underwent LAGB operation (21 women and 11 men) with a mean age of years = 33.77 (range 16 to 52 years), and of the 29 patients underwent LSG operation (22 women and 7 men) with a mean age of years = 33.86 (range 20 to 52 years) and of the 9 patients underwent LRYGB (7 women and 2 men) with a mean age of years= 35.11 (range 25 to 45 years). Thereafter patients were followed up monthly for the first 3 months postoperatively. Results: Using statistical Package for the Social Sciences Software (SPSS) version 15,we found the mean weight loss 1 month after surgery was 10.97kg (range 5-25 kg) for LAGB, 12.34 kg (range 6-21 kg) for LSG and 12.33 kg (range 10-20kg) for LRYGB. Mean weight loss 3 months after surgery was 18.81kg (range 7-38 kg) for LAGB, 22.48kg (range 10-59 kg) for LSG and 24.33kg (range 16-40kg) for LRYGB. Conclusion: The results from our study showed that all the studied procedures had a significant weight reduction rate in the first three months post operatively and that LRYGB is superior to the LAGB and LSG in weight reduction, although, all procedures are associated with marked weight loss. The age of the patients did not influence the decrease in BMI or affect the type of the procedure in weight reduction for the studied group. The results of this study do not diverge from those previously reported in the literature regarding the complications and the resolution or at least improvement of medical co-morbidities after these three procedures had been proved in this study. Keyword: laproscopy . Barialric, Surgery, Iraq.